Getting high to cope with COVID-19: Modelling the associations between cannabis demand, coping motives, and cannabis use and problems. (January 2022) - Vedelago, L.; Wardell, J.D.; Kempe, T.; Patel, H.; Amlung, M.; MacKillop, J.; Keough, M.T.
Highlights: Behavioural economic demand for a substance is linked with its use and misuse. People may be using cannabis to enhance mood or cope during the COVID-19 pandemic. Coping motives mediated the relationship between demand and cannabis problems. Abstract: During the COVID-19 pandemic, people may use substances like cannabis for enhancement or coping purposes. Behavioral economic demand for a substance is a key determinant of its use and misuse and can be measured via hypothetical purchase tasks. Previous research suggests that motivations to use a substance play a mediational role between elevated substance demand and problems, but comparable mechanistic research has yet to be done in the COVID-19 context and on the effects of cannabis demand on cannabis use patterns. Participants ( n  = 137) were recruited via the online crowdsourcing platform Prolific. Participants completed measures of cannabis use and problems, motivations for cannabis use, and the Marijuana Purchase Task. Two indices of demand, Persistence (i.e., sensitivity to increasing cost of cannabis) and Amplitude (i.e., consumption of cannabis at unrestricted cost), were related to increased cannabis problems via the use motive of coping during the COVID-19 pandemic. This model did not support the mediational role of enhancement motives. Those with increased cannabis demand who tend to use cannabis to cope are at increased risk of experiencing negative cannabis-related consequences during the COVID-19 pandemic.